คุณภาพน้ำจากระบบการเก็บกักน้ำฝนจากหลังคาในตำบลถ้ำใหญ่ อำเภอทุ่งสง จังหวัดนครศรีธรรมราช (WATER QUALITY OF ROOF RAINWATER HARVESTING SYSTEM IN THAMYAI, THUNG SONG DISTRICT, NAKHON SI THAMMARAT) - พิบูลย์ ปนัดดา; เจาะจิตต์ ศิริอุมา; สรเดช วรัญญา; มูฮัมหมัด อุษา (วารสารมหาวิทยาลัยศรีนครินทรวิโรฒ สาขาวิทยาศาสตร์และเทคโนโลยี, 2018)
การศึกษาครั้งนี้เป็นการวิเคราะห์คุณภาพน้ำในระบบเก็บกักน้ำฝนจากหลังคาในพื้นที่ชุมชนตำบลถ้ำใหญ่ อำเภอทุ่งสง จังหวัดนครศรีธรรมราช ซึ่งตั้งอยู่ในสภาพแวดล้อมที่อยู่ใกล้โรงงานอุตสาหกรรม ตัวอย่างน้ำในภาชนะเก็บกักน้ำฝน จำนวน 40 ครัวเรือน ถูกสุ่มตรวจในช่วงเดือนตุลาคม 2556 เพื่อวิเคราะห์ความขุ่น สี ความเป็นกรด-ด่าง ของแข็งละลายทั้งหมด ซัลเฟต และโคลิฟอร์มแบคทีเรีย ร่วมกับการสำรวจการปฏิบัติด้านสุขาภิบาลน้ำบริโภคของประชาชน ผลการศึกษาพบว่าคุณภาพน้ำฝนจากระบบเก็บกักน้ำจากหลังคามีค่าความเป็นกรด-ด่างและซัลเฟตอยู่เกณฑ์คุณภาพน้ำประปาดื่มได้ของกรมอนามัย พ.ศ. 2553 แต่พบการปนเปื้อนโคลิฟอร์มแบคทีเรียร้อยละ 100 และค่าความขุ่น สี ไม่ผ่านเกณฑ์ร้อยละ 17.5 และ 5 ตามลำดับ สาเหตุของการปนเปื้อนอาจมาจากหลายปัจจัย ได้แก่ ความไม่สะอาดของพื้นที่รับน้ำ (หลังคา ราง) และการปฏิบัติด้านสุขาภิบาลน้ำบริโภคของประชาชน โดยพบว่ามีครัวเรือนร้อยละ 67.5 มีการเก็บน้ำฝนแรกทันที ร้อยละ 65 ไม่ได้ทำความสะอาดภาชนะเก็บกักน้ำฝน ร้อยละ 47.5 ไม่มีการปิดฝาภาชนะเก็บกักน้ำฝน ผลการศึกษาครั้งนี้แสดงให้เห็นถึงปัญหาคุณภาพน้ำบริโภคจากระบบเก็กกักน้ำจากหลังคา ดังนั้นจึงควรมีการให้ข้อมูลแนวทางการสุขาภิบาลระบบเก็บกักน้ำฝนจากหลังคาแก่ประชาชนเพื่อสร้างความตระหนักเกี่ยวกับความปลอดภัยของน้ำบริโภค คำสำคัญ: ระบบเก็บกักน้ำฝนจากหลังคา คุณภาพน้ำ สุขาภิบาล This study involved analyses of roof rainwater harvesting systems at a rural housing society in Tambon Tumyai, Thung Song, Nakhon Si Thammarat, where locate near many industry plants. A total of 40 samples were collected from roofed rainwater tanks and analyzed for turbidity, color, pH, total dissolved solids, sulfate and coliforms on October, 2013. Additional information, including the domestic sanitation practice of people was examined. Analysis of harvested rainwater sample from residential roofs indicated that the measured pH and sulfate generally matched the Department of Health guideline of drinking water B.E. 2010. On the other hand, all water samples have positive for coliform bacteria, which is an important bacteriological parameter. Turbidity and color above the limit levels 17.5 and 5 percentage, respectively. The collected rainwater is contaminated by several factors include; the clean of rooftop catchment area and gutter and the sanitation practice of people. It was found that 67.5% of household do not use first flush diverters, 65% of household do not clean inside rainwater tank, 47.5% of household use rainwater storage tank with no lid. This result shows the poor quality of stored rainwater in rainwater tank of roof rainwater harvesting system. Therefore, it is necessary to promote safe sanitation practice and raise public awareness to addressing growing threats to drinking water quality. Keywords: Roof Rainwater Harvesting System, Water Quality, Sanitation